Pengaruh BI Rate (Suku Bunga Acuan) Terhadap Inflasi - Eman Singgih (Journal Of Communication Education, 2018)
ABSTRACTMeasurement of Inflation with CPI in Indonesia is grouped into 7 expenditure groups (based on theClassification of individual consumption by purpose - COICOP), namely: 1. Foodstuffs Group 2.Processed Foods, Beverages, Cigarettes and Tobacco Groups 3. Housing, Water, Electricity, Gas andFuel Groups 4. Clothing Groups 5. Health Groups 6. Education, Recreation and Sports Groups 7.Transport Groups, Communication and Financial Services. The 7 groups all touched the life needs of allIndonesian citizens living in the country. If it lasts long and continuously it will obviously affect thedifficulties of life. To overcome this, the monetary economic instrument must play an active role incontrolling inflation and play an effective role so that inflation can be stabilized through a policy ofadjusting Bank Indonesia's benchmark interest rate with the BI Rate. The BI Rate must be set by BankIndonesia as the central bank appropriately by taking into account the broad economic aspects andfostering optimism among economic actors. The magnitude of the BI rate is determined by the increaseor decrease of how many basis points the Bank Indonesia reference base serves as a reference for stateand private bank banks to determine the deposit interest rate and loan interest rates and others.Keywords: Inflation, BI rate.